(untitled) (Research, Society and Development, 2021)
This research aimed to evaluate the antibacterial activity of sunflower oil. This is an experimental research, developed in 2020. For the evaluation of the antimicrobial activity of sunflower oil, the diffusion disc method in solid medium and bacterial strains of Staphylococcus aureus, Enterococcus faecalis and klebsiela pneumoniae from American Type Culture were used Collection. The halo of bacterial growth inhibition formed by sunflower oil on the bacteria Staphylococcus aureus ATCC 25923 was 9 mm, for Enterococcus faecalis ATCC 29212 was 11 mm and for Klebsiela pneumoniae ATCC 13883 was 12 mm, conferring inhibition activity bacterial. The study points out that sunflower oil is a promising organic matter, and can be used by the nursing team in comprehensive care for human beings, as prevention of infections and skin recovery.